Liver safety assessment in clinical trials of new agents for chronic hepatitis B. Issue 2 (11th December 2019) - Fontana, Robert J.; Avigan, Mark I.; Janssen, Harry L. A.; Regev, Arie; Mishra, Poonam; Gaggar, Anuj; Brown, Nathaniel; Wat, Cynthia; Mendez, Patricia; Anderson, Ryan T.; Given, Bruce; Miller, Veronica; et al.
Abstract: Investigational agents that reduce or eliminate covalently closed circular DNA (cccDNA) or enhance host immunity against hepatitis B virus (HBV)‐infected hepatocytes are intended to induce a durable off‐treatment clearance of hepatitis B surface antigen (HBsAg) (referred to as functional cure). The aim of this paper was to highlight challenges in interpreting liver safety data in clinical trials of these agents when given alone or in combination regimens. The incidence, grading and management of spontaneous serum ALT flares in untreated chronic HBV patients are reviewed along with a summary of serum ALT flares observed during the registration trials for peginterferon and nucleos(t)ide reverse transcriptase inhibitors. Recommendations regarding the detection, management and interpretation of liver safety biomarker data in future clinical trials as well as suggested inclusion and exclusion criteria for phase 1/2 vs phase 3 studies are provided. Criteria to help classify liver safety signals as being due to the intended therapeutic response, emergence of drug‐resistant HBV virions, or idiosyncratic drug‐induced liver injury are provided along with a review of the role of an expert hepatic adjudication panel in assessing a compound's hepatotoxicity profile. Finally, an algorithmic approach to the differential diagnosis and recommended medical evaluation and management of individual clinical trial patients that develop a liver safety signal is provided along with the rationale to collect and test research blood samples for future mechanistic studies.